Edouard Borovansky and Laurel Martyn in Façade, Borovansky Ballet - Hall, Hugh P. (1943)
Choreography by Laurel Martyn after Frederick Ashton, design by William Constable.
Title devised by cataloguer based on caption list prepared by researcher.
Condition: Good.
"7P/5"--In pencil on front; "Facade; Boro & Laurel"--In pencil on verso.
Part of the collection: Geoffrey Ingram archive of Australian ballet.
Also available online
Keywords: Borovansky, Edouard, -- 1902-1959 -- Photographs; Martyn, Laurel, -- 1916-2013 -- Photographs; Borovansky Ballet -- Performances -- Photographs; Facade (Choreographic work: Martyn after Ashton) -- Photographs; Ballet -- Australia -- Photographs; Ballet dancers -- Australia -- Portraits; Ballet dancers